Colloidal interaction forces drive the selective separation of scheelite and calcite: a kinetics and AFM study - Wenjuan Sun; Guolei Liu; Ruolin Wang; Yujia Tian; Zhen Ye; Xujia Cao; Haisheng Han (Minerals Engineering, 2026)

Multi-class urinary antibiotic exposure, dietary sources, and childhood overweight and obesity risk through lipid metabolic disruption: evidence from multicenter cohorts in China - Xinli Song; Jieyu Liu; Li Chen; Yi Zhang; Ruolin Wang; Jianuo Jiang; Lan Zhang; Yanle Xiong; Jingyang Su; Ziqi Dong; Yang Qin; Dengcheng Zhang; et al. (Environmental Pollution, 2026)

In-situ transformation of layered double hydroxide precursors into CeF3@Ni3Fe catalysts via anion-mediation for hydrogen storage in MgH2 - Mei Tang; Jiakun Yang; Ruolin Zhao; Xiuyu Yue; Haizhen Liu; Jin Guo; Zhiqiang Lan (Chemical Engineering Journal, 2026)

Life-time levonorgestrel exposure causes intergenerational alterations of the thyroid-catecholaminergic–GABAergic functional network in zebrafish (Danio rerio) - Xing Hu; Qianlin Cai; Junhao Wu; Meixin Ye; Jinlin Yang; Hao Huang; Weiyi Liang; Yutong Zhang; Ruolin Shi; Yazi Liu; Liping Hou; Diyun Chen (Environmental Research, 2026)

Structure-based classification for differential tyrosine kinase inhibitors efficacy of EGFR exon 19 deletions in non-small cell lung cancer - Wei Zhuang; Hua Bai; Jie Zhao; Weihua Li; Jiaojiao Yu; Zhijie Wang; Jianchun Duan; Xuezhi Hao; Yan Wang; Yutao Liu; Lin Wang; Lin Lin; et al. (Science China Life Sciences, 2026)

SEMA4A promotes acute myeloid leukemia progression through inhibiting apoptosis - Xinyu Li; Binyu Yao; Meiling Sun; Wangshi Li; Xingzhi Lv; Keyang Luo; Yue Wu; Ruolin Xiu; Yuzhu Ma; Fukai Liu; Yanhong Zhao; Shengjin Fan; et al. (Genes & Genomics, 2026)

CeO2 nanoparticles-embedded hierarchical porous C/SiO2 for efficient catalytic amine regeneration in CO2 capture - Ling Liu; Yunrong Zhang; Yingying Zhang; Qi Dong; Yanyang Xue; Wanyi Ding; Fei Yang; Guo-Jun Kang; Ruolin Cheng; Shi-Jian Lu (Journal of Environmental Chemical Engineering, 2026)

Biocontrol of Apple Valsa Canker by Bacillus sp. H12 and modulation of the apple seedlings microbiome - Ling Sun; Jianxin Gao; Yawen Tan; Yiting Xia; Ruolin Wang; Ruiqi Liu; Xinmei Zhang; Xia Yan; Lili Huang (Pesticide Biochemistry and Physiology, 2026)

Flame evolution behavior of syngas/air mixtures with a large range of equivalence ratios: Examination from the perspective of dynamics and thermal effects - Bin Su; Yuwei Wang; Zhenmin Luo; Ruolin Hao; Litao Liu; Shangyong Zhou; Tao Wang (Fuel, 2026)

Flammability limits and near-limit kinetic behaviors of multi-component syngas: A combined experimental and numerical study - Zhenmin Luo; Ruolin Hao; Bin Su; Lu Liu; Dinghan Li; Litao Liu; Shangyong Zhou; Tao Wang (Fuel, 2026)

Co-modulation of overall compressibility and conductive networks on individual sensing unit for high-performance flexible tactile sensors - Yifan Liu; Zheming Zhang; Xiao Xu; Fengming Hu; Ruolin Liu; Rongmei Wang; Ming Lei; Ziyi Dai; Bingpu Zhou (Chemical Engineering Journal, 2026)

Regulation of phenazine-1-carboxylic acid synthesis by hmgL in Pseudomonas chlororaphis and its role in restructuring plant microbiomes for disease resistance - Ruolin Wang; Boya Liu; Yutong Wu; Yu Wang; Xiaoyu Xia; Xia Yan; Lili Huang (Pesticide Biochemistry and Physiology, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Adsorption of chlorogenic acid in aqueous solution of Chrysanthemum morifolium (Chuju) by walnut shell-derived biochar - Ying Gao; Nan Zhang; Xinran Xu; Ruolin Zhang; Jiahang Liu; Zongyao Qian; Xuelian Wang; Yunbin Qin (Food Chemistry, 2025)

Evaluation of the Degradation Effect of Zearalenone in feed by Bacillus amyloliquefaciens H6 and its Detoxification in Mice - Ruolin Wang; Kaiwei Geng; Yuxuan Liu; Yang Liu; Yujie Gong; Ruirui Jiang; Yadong Tian; Xiangtao Kang; Xiangli Sun; Yanbin Wang (Current Microbiology, 2025)

Per- and polyfluoroalkyl substances and platelet-related hematotoxicity: An integrated study of in silico, toxicological, and population evidence - Dihui Xu; Jie Xiang; Ruolin Qin; Zhijian Chen; Xiaofeng Wang; Peiwei Xu; Yitao Pan; Xinhan Zhang; Yan Wang; Ping Cheng; Yuan Chen; Dandan Xu; et al. (Journal of Hazardous Materials, 2025)

Red blood cell-mimetic hollow covalent organic framework with oxygen-replenishing and cavitation-amplified for enhanced sonodynamic therapy of periodontitis - Yang Zhou; Qiyuan Pan; Ruolin Wang; Yan Ge; Xiao Zhang; Yifan Guo; Rongyin Sun; Xianglong Liu; Sainan Liu; Min Liu; Jun Lin (Chemical Engineering Journal, 2025)

The impact of increased water hardness on pollutant toxicity in freshwater aquatic organisms - Guangchao Shi; Jiawei Wang; Jianwei Yu; Sida Qin; Ruolin Liu; Dan Wu (Environmental Monitoring and Assessment, 2025)

Luminescence dating of core sediments from the southern coastal Bohai Sea, China, and its implications for transgression history during the Late Quaternary - Zhiqiang Xu; Yang Han; Bingpeng Yan; Mingbo Li; Ruolin Jiang; Ruonan Tian; Bohui Liu; Zihui Zhu; Weitao Yuan; Zhongping Lai (Frontiers in Marine Science, 2025)
Several marine strata have developed along the southern coastal Bohai Sea since the Late Quaternary, preserving abundant records of sedimentary evolution. This region is ideal for studying the sedimentary history of a river–sea interaction area. However, detailed sedimentological and chronological studies remain limited, mainly focusing on the estuaries of the Mihe River. In this study, 12 optically stimulated luminescence (OSL) samples were collected from the upper 20 m of a 101 m core to establish a chronological framework using quartz OSL dating. Grain-size analysis was also conducted to determine sedimentological characteristics. Results indicate that the quartz OSL ages range from >100 ka to 6.2 ± 0.4 ka, and we believe they were the minimum ages when equivalent dose (D e ) >ca. 250 Gy (sample DZK3-G07 and below) owing to OSL signal saturation. Our findings reveal a sedimentary hiatus between >100 ka and 19.8 ka. Holocene sediments are found above a depth of 8.4 m with an onset age of approximately 10.5 ka. A lacustrine layer (8.4–9.6 m) in core DZK3 was dated to 19.8–10.5 ka, which is much older than that of the limnetic and lagoon layers in other cores in this area. Based on sedimentary facies and dating results, no transgressive sediments were observed during marine isotope stage (MIS) 3, and T2 (Xianxian transgression) in the southern coastal Bohai Sea only occurred in MIS 5e. This sedimentary sequence pattern is consistent with global sea-level changes.

Meta-analysis of electro-Fenton degradation efficiency: Unraveling the impacts of process parameters and cathode materials - Jiawei Wang; Guangchao Shi; Ruolin Liu; Shuhan Liu; Yuhan Zhang; Jianwei Yu; Dan Wu (Journal of Water Process Engineering, 2025)

Recycling of MSWI fly ash into low-carbon supersulfated composites - Yan Xia; Zhenye Liu; Lei Wang; Ruolin Zhao; Gang Huang; Yaqian Shi; Yirou Zhou; Jianhua Yan (Chemical Engineering Journal, 2025)

Fluoroquinolone antibiotics trigger selective oxidation in the trace-Cu(II)/peroxydisulfate system: The synergistic effect of dual reactive sites in chemical structure - Jiahang Liu; Xiaoyang Li; Ruolin Lv; Yingying Chu; Mengying Qian; Weiming Zhang (Journal of Hazardous Materials, 2025)

Electron beam irradiation coupled ultrasound-assisted natural deep eutectic solvents extraction: A green and efficient extraction strategy for proanthocyanidin from walnut green husk - Heting Qi; Wanjia Fu; Yujie Liu; Junqing Bai; Ruolin Wang; Guangming Zou; Heyu Shen; Yingying Cai; Anwei Luo (Food Chemistry, 2025)

Equivalent spring model and efficient numerical strategy for simulating mechanical performance of seam-clip connections in aluminum alloy high-vertical standing seam metal cladding systems - Qisheng Liang; Qingshan Yang; Min Liu; Ruolin Liu; Wei Chen (Engineering Structures, 2025)

Occurrence and migration patterns of microplastics in different tidal zones of tourist beaches: A case study in the Bohai Bay, North China - Yutao Zuo; Yawen Ge; Ruolin Wang; Wanqiang Xu; Changhong Liu; Zixiao Guo; Shuo Wang; Huiyuan Jia; Yuecong Li (Journal of Environmental Management, 2024)

Design and construction of an artificial labor-division consortium for phenanthrene degradation with three-functional modules - Yiyang Liu; Ruolin Qin; Xiaoqiang Jia (Chemosphere, 2024)

Dead Fish Detection Model Based on DD-IYOLOv8 - Jianhua Zheng; Yusha Fu; Ruolin Zhao; Junde Lu; Shuangyin Liu (Fishes, 2024)
In aquaculture, the presence of dead fish on the water surface can serve as a bioindicator of health issues or environmental stressors. To enhance the precision of detecting dead fish floating on the water’s surface, this paper proposes a detection approach that integrates data-driven insights with advanced modeling techniques. Firstly, to reduce the influence of aquatic disturbances and branches during the identification process, prior information, such as branches and ripples, is annotated in the dataset to guide the model to better learn the scale and shape characteristics of dead fish, reduce the interference of branch ripples on detection, and thus improve the accuracy of target identification. Secondly, leveraging the foundational YOLOv8 architecture, a DD-IYOLOv8 (Data-Driven Improved YOLOv8) dead fish detection model is designed. Considering the significant changes in the scale of dead fish at different distances, DySnakeConv (Dynamic Snake Convolution) is introduced into the neck network detection head to adaptively adjust the receptive field, thereby improving the network’s capability to capture features. Additionally, a layer for detecting minor objects has been added, and the detection head of YOLOv8 has been modified to 4, allowing the network to better focus on small targets and occluded dead fish, which improves detection performance. Furthermore, the model incorporates a HAM (Hybrid Attention Mechanism) in the later stages of the backbone network to refine global feature extraction, sharpening the model’s focus on dead fish targets and further enhancing detection accuracy. The experimental results showed that the accuracy of DD-IYOLOv8 in detecting dead fish reached 92.8%, the recall rate reached 89.4%, the AP reached 91.7%, and the F1 value reached 91.0%. This study can achieve precise identification of dead fish, which will help promote the research of automatic pond patrol machine ships.

Flame propagation dynamic characteristics and mechanisms of methane–syngas–air mixtures in a semi-enclosed duct - Lu Liu; Zhenmin Luo; Bin Su; Ruolin Hao; Tao Wang; Jun Deng; Fangzhi Song (Fuel, 2024)

Valorization of municipal solid waste incineration fly ash in low-carbon alkali-activated materials - Yan Xia; Zhenye Liu; Zhenhao Song; Ruolin Zhao; Jinpeng Wu; Lei Wang; Jianhua Yan (Chemical Engineering Journal, 2024)

Physiological properties evaluation and exopolysaccharide biosynthesis of Limosilactobacillus fermentum JL-2 from Chinese traditional fermented dairy product based on genomic insight - Ruolin Yuan; Lai Jiang; Ruonan Liu; Yanfeng Tuo; Guangqing Mu; Shujuan Jiang (Food Bioscience, 2024)

Effectiveness of cawthorne-cooksey exercises in wallenberg syndrome-induced central vertigo - Na Ye; Zhao Ma; Xuyao Wang; Ruolin Liu; Xin Gu (Acta Neurologica Belgica, 2024)

An efficient photo-Fenton In2O3@FeIn2S4 composite catalyst for tetracycline degradation - Shengyu Jing; Jing Ren; Anhu Wang; Ruolin Cheng; Huagen Liang; Hai Liu; Fu Chen; Panagiotis Tsiakaras (Chemical Engineering Journal, 2024)

Association of the external environmental exposome and obesity: A comprehensive nationwide study in 2019 among Chinese children and adolescents - Li Chen; Yang Qin; Yi Zhang; Xinli Song; RuoLin Wang; Jianuo Jiang; Jieyu Liu; Tongjun Guo; Wen Yuan; Zhiying Song; Yanhui Dong; Yi Song; et al. (Science of The Total Environment, 2024)

Differentiated impacts of short-term exposure to fine particulate constituents on infectious diseases in 507 cities of Chinese children and adolescents: A nationwide time-stratified case-crossover study from 2008 to 2021 - Li Chen; Wen Yuan; Mengjie Geng; Rongbin Xu; Yi Xing; Bo Wen; Yao Wu; Xiang Ren; Yue Shi; Yi Zhang; Xinli Song; Yang Qin; et al. (Science of The Total Environment, 2024)

Association of maternal blood high-mobility group box 1 levels and adverse pregnancy outcomes: A systematic review and meta-analysis - Liping Xue; Ruolin Chen; Ying Liu; Peiguang Niu; Jintuo Zhou; Jinhua Liu; Jinhua Zhang; Huajiao Chen (Reproductive Biology, 2024)

Machine learning: An accelerator for the exploration and application of advanced metal-organic frameworks - Ruolin Du; Ruiqi Xin; Han Wang; Wenkai Zhu; Rui Li; Wei Liu (Chemical Engineering Journal, 2024)

Iron-rich industrial waste enhanced low-carbon radiation shielding functional composites - Yan Xia; Daquan Shi; Ruolin Zhao; Kunyang Yu; Minghao Liu; Hengjun Mei; Lei Xu; Yading Zhao; Lei Wang; Jianhua Yan (Journal of Cleaner Production, 2024)

A novel method to quantify chitosan in aqueous solutions by ultrahigh-performance liquid chromatography–tandem mass spectrometry - Ting Xue; Lei Zhou; Fanjun Wang; Zhuang Tian; Nanxi Li; Tong Ye; Ruolin Hao; Lei Yang; Ruolan Gu; Hui Gan; Zhuona Wu; Xiaoxia Zhu; et al. (Carbohydrate Polymers, 2024)

Oxidation of emerging contaminants by S(IV) activated ferrate: Identification of reactive species - Yingying Chu; Mujian Xu; Xiaoyang Li; Junhe Lu; Zhichao Yang; Ruolin Lv; Jiahang Liu; Lu Lv; Weiming Zhang (Water Research, 2024)

TRPA1-PI3K/Akt-OPA1-ferroptosis axis in ozone-induced bronchial epithelial cell and lung injury - Jiali Weng; Qi Liu; Chenfei Li; Yi Feng; Qing Chang; Meiqin Xie; Xiaohui Wang; Mengnan Li; Hai Zhang; Ruolin Mao; Na Zhang; Xiaohua Yang; et al. (Science of The Total Environment, 2024)

Responses of plant immune system and rhizosphere soil microbiome to the elicitor BAR11 in Arabidopsis thaliana - Ruolin Wang; Yu Wang; Dandan He; Tiecheng Shi; Yanan Zhang; Shang Liu; Xia Yan; Lili Huang (Science of The Total Environment, 2024)

Exploring the associations between phthalate exposure and cardiometabolic risk factors clustering among children: The potential mediating role of insulin-resistant-related genes DNA methylation - Jieyu Liu; Jieyun Song; Di Gao; Yanhui Li; Tongjun Guo; Wen Yuan; Manman Chen; Li Chen; Yi Zhang; Qi Ma; Mengjie Cui; Xinli Song; et al. (Journal of Hazardous Materials, 2024)

An Underwater Image Restoration Deep Learning Network Combining Attention Mechanism and Brightness Adjustment - Jianhua Zheng; Ruolin Zhao; Gaolin Yang; Shuangyin Liu; Zihao Zhang; Yusha Fu; Junde Lu (Journal of Marine Science and Engineering, 2023)
This study proposes Combining Attention and Brightness Adjustment Network (CABA-Net), a deep learning network for underwater image restoration, to address the issues of underwater image color-cast, low brightness, and low contrast. The proposed approach achieves a multi-branch ambient light estimation by extracting the features of different levels of underwater images to achieve accurate estimates of the ambient light. Additionally, an encoder-decoder transmission map estimation module is designed to combine spatial attention structures that can extract the different layers of underwater images’ spatial features to achieve accurate transmission map estimates. Then, the transmission map and precisely predicted ambient light were included in the underwater image formation model to achieve a preliminary restoration of underwater images. HSV brightness adjustment was conducted by combining the channel and spatial attention to the initial underwater image to complete the final underwater image restoration. Experimental results on the Underwater Image Enhancement Benchmark (UIEB) and Real-world Underwater Image Enhancement (RUIE) datasets show excellent performance of the proposed method in subjective comparisons and objective assessments. Furthermore, several ablation studies are conducted to understand the effect of each network component and prove the effectiveness of the suggested approach.

Alteration of chromite during serpentinization of peridotites - Ruolin Liu; Junhong Zhao; Meifu Zhou; Han Qi (Lithos, 2023)

An autocatalytic Fe(III)/H2O2 Fenton-like process triggered by tetracycline: The overlooked effect of quinone intermediates - Jiahang Liu; Xiaoyang Li; Yingying Chu; Ling Yuan; Ruolin Lv; Weiming Zhang (Chemical Engineering Journal, 2023)

Effect of MOF-derived carbon–nitrogen nanosheets co-doped with nickel and titanium dioxide nanoparticles on hydrogen storage performance of MgH2 - Zhiqiang Lan; Feifan Hong; Weitao Shi; Ruolin Zhao; Renhuan Li; Yi Fan; Haizhen Liu; Wenzheng Zhou; Hua Ning; Jin Guo (Chemical Engineering Journal, 2023)

Reproductive toxicity of microplastics in female mice and their offspring from induction of oxidative stress - Yingbing Zhang; Xiyue Wang; Yifan Zhao; Jianglin Zhao; Tong Yu; Yupei Yao; Ruolin Zhao; Ruiluan Yu; Jun Liu; Jianmin Su (Environmental Pollution, 2023)

Photocatalytic CO2 cycloaddition over highly efficient W18O49-based composites: An economic and ecofriendly choice - Ruolin Cheng; Anhu Wang; Shuxun Sang; Huagen Liang; Shiqi Liu; Panagiotis Tsiakaras (Chemical Engineering Journal, 2023)

The effect of TiO2NPs on cloransulam-methyl toxicity to earthworm (Eisenia fetida) - Ruolin Wu; Hunan Liu; Chengbo Lu; Kaixuan Hou; Xiaole Wang; Jun Wang; Zhongkun Du; Bing Li; Lusheng Zhu; Jinhua Wang (Chemosphere, 2023)

Novel carbon-coated zirconium oxide nanocomposites enable ultrahigh oxidant utilization efficiency for selective degradation of organic contaminants - Xiaoyang Li; Jiahang Liu; Ruolin Lv; Yingying Chu; Lu Lv; Junhe Lu; Weiming Zhang (Chemical Engineering Journal, 2023)

Quantitative trait loci for rolled leaf in a wheat EMS mutant from Jagger - Ruolin Bian; Na Liu; Yuzhou Xu; Zhenqi Su; Lingling Chai; Amy Bernardo; Paul St. Amand; Allan Fritz; Guorong Zhang; Jessica Rupp; Eduard Akhunov; Katherine W. Jordan; et al. (Theoretical and Applied Genetics, 2023)

Let-7c-5p down-regulates immune-related CDCA8 to inhibit hepatocellular carcinoma - Wanjin Chen; Haibo Wang; Yuanlong Shen; Shouwen Wang; Deng Liu; Hongchuan Zhao; Guobin Wang; Fan Huang; Wei Wang; Ruolin Wu; Liujin Hou; Zhenghui Ye; et al. (Functional & Integrative Genomics, 2023)

Amorphous zirconium oxide activates peroxymonosulfate for selective degradation of organic compounds: Performance, mechanisms and structure-activity relationship - Xiaoyang Li; Ruolin Lv; Weiming Zhang; Mingyang Li; Junhe Lu; Yi Ren; Yue Yin; Jiahang Liu (Water Research, 2023)

An R2R3-MYB FtMYB11 from Tartary buckwheat has contrasting effects on abiotic tolerance in Arabidopsis - Qian Chen; Lu Peng; Anhu Wang; Lingzhi Yu; Yu Liu; Xinrong Zhang; Ruolin Wang; Xiaoyi Li; Yi Yang; Xufeng Li; Jianmei Wang (Journal of Plant Physiology, 2023)

PLAGL2 increases adriamycin resistance and EMT in breast cancer cells by activating the Wnt pathway - Yuxiao Li; Ruolin Liu; Xingzhao Han; Wei Xu; Yahui Liu (Genes & Genomics, 2023)

Multi-Degree-of-Freedom for Underwater Optical Wireless Communication with Improved Transmission Performance - Anliang Liu; Ruolin Zhang; Bin Lin; Hongxi Yin (Journal of Marine Science and Engineering, 2022)
Underwater optical wireless communication (UOWC) has great potential to provide high-speed and intensive communications over short ranges underwater. However, the mobility of the UOWC system is limited by the strict alignment requirements between the transceivers. In this paper, a multi-degree-of-freedom (MDOF) UOWC system with high flexibility and improved transmission performance is proposed and experimentally demonstrated based on the off-the-shelf light-emitting diode (LED) source. A hardware pre-equalization circuit is employed at the transmitter to extend the modulation bandwidth from 5.03 MHz to 50 MHz. At the receiving end, a Fresnel lens array is constructed to achieve efficient convergence of multiple incident optical signals from different directions. To improve the underwater signal transmission quality, we designed an additional digital signal recovery module after the trans-impedance amplifier. Finally, an experimental system is established with a 460 nm blue LED. The communication reliability of the system is verified by the measurement of the eye diagram and the bit error rate of the recovered signal at the receiving end. The experimental results show that optical signals from three different incident directions with a maximum data rate of 100 Mbps are reliably transmitted over a 1.2-m-long water tank using the non-return-to-zero on-off-keying modulation format.

Early warning model for death of sepsis via length insensitive temporal convolutional network - Minghui Gong; Jingming Liu; Chunping Li; Wei Guo; Ruolin Wang; Zheng Chen (Medical & Biological Engineering & Computing, 2022)

Induced sputum metabolomic profiles and oxidative stress are associated with chronic obstructive pulmonary disease (COPD) severity: potential use for predictive, preventive, and personalized medicine - Tao Zhu; Shanqun Li; Jiajia Wang; Chunfang Liu; Lei Gao; Yuzhen Zeng; Ruolin Mao; Bo Cui; Hong Ji; Zhihong Chen (EPMA Journal, 2020)
Chronic obstructive pulmonary disease (COPD) is a highly heterogeneous disease, and metabolomics plays a hub role in predictive, preventive, and personalized medicine (PPPM) related to COPD. This study thus aimed to reveal the role of induced sputum metabolomics in predicting COPD severity. In this pilot study, a total of 20 COPD patients were included. The induced sputum metabolites were assayed using a liquid chromatography-mass spectrometry (LC-MS/MS) system. Five oxidative stress products (myeloperoxidase (MPO), superoxide dismutase (SOD), glutathione (GSH), neutrophil elastase (NE), and 8-iso-PGF2α) in induced sputum were measured by ELISA, and the metabolomic profiles were distinguished by principal component analysis (PCA) and orthogonal projections to latent structures discriminant analysis (OPLS-DA). The Kyoto Encyclopedia of Genes and Genomes (KEGG) was used for pathway enrichment analysis, and a significant difference in induced sputum metabolomics was observed between moderate and severe COPD. The KEGG analysis revealed that the glycerophospholipid metabolism pathway was downregulated in severe COPD. Due to the critical role of glycerophospholipid metabolism in oxidative stress, significant negative correlations were discovered between glycerophospholipid metabolites and three oxidative stress products (SOD, MPO, and 8-iso-PGF2α). The diagnostic values of SOD, MPO, and 8-iso-PGF2α in induced sputum were found to exhibit high sensitivities and specificities in the prediction of COPD severity. Collectively, this study provides the first identification of the association between induced sputum metabolomic profiles and COPD severity, indicating the potential value of metabolomics in PPPM for COPD management. The study also reveals the correlation between glycerophospholipid metabolites and oxidative stress products and their value for predicting COPD severity.

Isotopic fingerprinting of dissolved iron sources in the deep western Pacific since the late Miocene - Ruolin Liu; Bai Guo; Maoyu Wang; Weiqiang Li; Tao Yang; Hongfei Ling; Tianyu Chen (Science China Earth Sciences, 2020)

Effect of enhancers on the phytoremediation of soils polluted by pyrene and Ni using Sudan grass (Sorghum sudanense (Piper) Stapf.) - Xiaoyan Liu; Siyuan Shen; Xinying Zhang; Xintong Chen; Ruolin Jin; Xinyi Li (Environmental Science and Pollution Research, 2020)

Decadal change in summer precipitation over the east of Northwest China and its associations with atmospheric circulations and sea surface temperatures - Shasha Shang; Gaofeng Zhu; Ruolin Li; Jie Xu; Juan Gu; Huiling Chen; Xiaowen Liu; Tuo Han (International Journal of Climatology, 2020)
As global warming has progressed, precipitation patterns over arid Northwest China have undergone significant change. In this study, changes in summer (JJA) precipitation over the eastern part of Northwest China (ENWC) from 1980 to 2014 were investigated using the China gridded monthly precipitation dataset (CN05.1). The results showed that summer precipitation over the ENWC experienced a decadal wet‐to‐dry shift in 1998. Westerlies played an important role in the upper atmospheric levels in terms of water vapour transport; the decadal variations in summer precipitation were principally controlled by the water vapour input from the ENWC's western boundary. In addition, the decadal variations in summer precipitation in the ENWC appear to be associated with a meridional teleconnection around 110°E and a zonal pattern over 45–60°N in the lower troposphere. These two teleconnections led to cyclonic anomalies in the ENWC and enhanced water vapour transport into the ENWC, resulting in above‐normal precipitation during the 1989–1998 decadal period. Further, the warmer (colder) sea surface temperatures (SSTs) observed in the tropical Eastern Pacific correspond to the southward (northward) displacement of the Asian jet stream and a negative (positive) phase of the Silk Road pattern, resulting in a wet (dry) ENWC. Moreover, the SST anomalies in the North Atlantic and Northwest Pacific may affect summer precipitation over the ENWC via a zonal teleconnection in the middle troposphere.

Anaerobic digestion of tobacco stalk: biomethane production performance and kinetic analysis - Lyu Li; Ruolin Wang; Zhenlai Jiang; Wanwu Li; Guangqing Liu; Chang Chen (Environmental Science and Pollution Research, 2019)

Extracellular ATP promoted pollen germination and tube growth of Nicotiana tabacum through promoting K+ and Ca2+ absorption - Yansheng Wu; Baozhi Qin; Kaili Feng; Ruolin Yan; Erfang Kang; Ting Liu; Zhonglin Shang (Plant Reproduction, 2018)

Association between non-steroidal anti-inflammatory drug use and melanoma risk: a meta-analysis of 13 studies - Shan Li; Yanqiong Liu; Zhiyu Zeng; Qiliu Peng; Ruolin Li; Li Xie; Xue Qin; Jinmin Zhao (Cancer Causes & Control, 2013)